(untitled) (Research, Society and Development, 2020)
This article aims to isolate, identify and screen phytochemistry a prepared extract of the fungus Penicillium purpurogenum, obtained from a polluted marine environment of São Luís-MA. The research was conducted at Laguna da Jansen located in the municipality of São Luís, Maranhão, Brazil. Four sediment collections were performed from May to September 2017, in the morning period. The samples were obtained from a depth of up to 73.5 cm with the aid of a metal dredger. The identification of the fungus followed methodologies of isolation and identification with phytochemical screening of extracts prepared by Matos methodology. Identification confirmed the presence of Penicillium purpurogenum. Phytochemical screening of extracts exhibited the presence of substance phenols, alkaloids, triterpenes, flavanones, flavanols, catechins, flavonoids and steroids, being of interest in the study of biological activities to be performed with the extracts obtained from the fungus under study. Finally, the results obtained in this study ensure a class of chemical constituents, identified by phytochemical screening, which encourage studies of biological activities with the extracts obtained ensuring a potential for applicability of the bioproduct.